How to Make Grants a Better Match for Private Sector Development - World Bank (World Bank, Washington, DC, 2017)
Matching grants (MGs) have been implemented by the World Bank for over two decades. They remain a very popular instrument for private sector development interventions, despite often challenging implementation and insufficient evidence of impact. The objective of this study is to synthesize the current knowledge on MGs and to review the experience with this instrument, as designed and implemented by the World Bank from the early 1990s to the present. In doing so, we hope to equip teams in charge of ongoing and planned MG operations with a better understanding of the instrument and to help them choose the design and implementation arrangements that are best fitted to their objectives. The authors look at both the ‘why’ and the ‘how’ of MG programs, focusing on those aiming to foster private sector development and small and medium enterprises (SMEs) competitiveness primarily through the use of business development services (BDS). The authors also look at how success is defined and question the way the outcome of MG programs is often assessed. While 75 percent of projects in the sample were deemed to have some degree of success, the definition of success rarely reflects a measurement of broad and sustainable economic benefits that will justify the subsidization of private enterprises with public funds. We argue that this is linked to a common weakness in identifying a sound economic rationale, such as a specific market failure to be solved, and in subsequently not focusing the design and measurement of the MG on the fund’s additionality beyond the private benefit of recipients. The authors conclude that a robust definition of the economic rationale is a critical prerequisite for the use of MG programs and should include, among others, an identification of a specific market failure, consideration of alternative instruments, cost-benefit analysis, assessment of the potential for additionality and spillovers, and a realistic exit strategy. The authors recommend an equally robust monitoring and evaluation (M&E) system tied directly to the economic rationale, which is essential for real-time assessment of impact, potential course correction, and learning, and could be utilized to gauge additionality and sustainability. Increased attention to these elements could help teams make the most of this potentially powerful instrument for private sector development and competitiveness.